Dynamic analysis of landscape changes in the Heihe River Basin using remote sensing and GIS - Haoyu Wang; Yaowen Xie; Yingying Wu (2010 18th International Conference on Geoinformatics, 2010)
Landscape spatial pattern is one of the main study fields in landscape ecology, as well in land use and land cover change studies. The formation and variation of landscape pattern are considered as the composite reactions of the area ecological environment quality, which come from mufti-factors interaction of nature and man-made. Heihe River Basin is the second largest endorheic drainage in the northwest of China; it is the typical arid inland river basin with desertscape. This paper is aimed to intensively study the drive mechanism of landscape pattern changes, and then provides a reference for the environmental protection and construction of Heihe region. Based on remote sensing and geographic information system, interpreting the 2000 and 2009's Landsat TM data, the landscape patterns were divided into six categories: arable land, forest, grass, aquatorium, residential area and unused land, then using the spatial pattern analysis software Fragstats to calculate the landscape pattern indices chose from class and landscape level. At last, these indices from two periods were analyzed by quantitative indicators. The results showed that: the area ratio of unused land and grassland exceeds 73% and 15% respectively; the desert landscape to which they were subject is the main landscape of Heihe River Basin, after the unused land and grassland are arable land, forest land, aquatorium and residential area. Unused land's absolute advantage of area ratio and largest patch index determined the landscape ground substance of Heihe River Basin. Landscape pattern of Heihe River Basin showed different changes from 2000 to 2009, the area of arable land, forest land, aquatorium and residential area increased 9.8%, 4.4%, 34.8% and 4.7% respectively; on the other hand, the area of grassland and unused land declined 3.5%, 0.6% respectively. The fragmentation of arable land, forest land, grassland and unused land decreased, residential area and aquatorium's increased. The whole landscape of Heihe River Basin was strongly influenced by human activities, so the Shannon's diversity index (SHDI) rose from 0.8601 to 0.9568, Shannon's evenness index (SHEI) rose from 0.48 to 0.534, aggregation indices (AI) in these two years were both greater than 98, division (DIVISION) reduced from 0.5415 to 0.4832, perimeter-area fractal dimension (PAFRAC) reduced from 1.4007 to 1.3479. Each patch type became equalized, and the total heterogeneity lowered. The dominance of unused land reduced slightly, the differences between each class's area ratios decreased, and these classes distributed more evenly. The exclusiveness of classes is powerful. The number of large patches decreased which turned into smaller patches. The self-similarity of patches became more intensive; its shape became more regular and tends to be simple. Component of ground substance reduced and its control function over landscape pattern diminished.